Effects of rumen cannulation combined with different pre-weaning feeding intensities on the intestinal, splenic and thymic immune system in heifer calves several month after surgery - Liermann, Wendy; Tümmler, Lisa-Maria; Kuhla, Björn; Viergutz, Torsten; Hammon, Harald Michael (Frontiers in Immunology, 2023)
Fistulation is a helpful procedure in animal nutritional research and also common practise in human medicine. However, there are indications that alterations in the upper gastrointestinal tract contribute to intestinal immune modulations. The present study aimed to investigate effects of a rumen cannulation in week 3 of life on the intestinal and tissue specific immune system of 34-week old heifers. Nutrition influences the development of the neonatal intestinal immune system to a high extent. Therefore, rumen cannulation was investigated in combination with different pre-weaning milk feeding intensities (20% (20MR) vs. 10% milk replacer feeding (10MR)). Heifers of 20MR without rumen cannula (NRC) showed higher cluster of differentiation (CD)8+ T cell subsets in mesenteric lymph nodes (MSL) compared to heifers with rumen cannula (RC) and 10MRNRC heifers. CD4+ T cell subsets in jejunal intraepithelial lymphocytes (IELs) were higher in 10MRNRC heifers compared to 10MRRC heifers. CD4+ T cell subsets in ileal IELs were lower and CD21+ B cell subsets were higher in NRC heifers compared to RC heifers. CD8+ T cell subsets in spleen tended to be lower in 20MRNRC heifers compared to all other groups. Splenic CD21+ B cell subsets were higher in 20MRNRC heifers compared to RC heifers. Splenic toll like receptor (TLR) 6 expression was increased and IL4 expression tended to be increased in RC heifers than NRC heifers. Splenic TLR2, 3 and 10 gene expression was higher in 20MR compared to 10MR heifers. Jejunal prostaglandin endoperoxide synthase 2 expression was higher in RC heifers than NRC heifers, and MUC2 expression tended to increase in 20MR heifers compared to 10MR heifers. In conclusion, rumen cannulation modulated T and B cell subsets in the down streaming gastrointestinal tract and spleen. Pre-weaning feeding intensity seemed to affect intestinal mucin secretion and T and B cell subsets in MSL, spleen and thymus until several month later. Interestingly, in MSL, spleen and thymus the 10MR feeding regime evoked similar modulations of T and B cell subsets like rumen cannulation.